2009
DOI: 10.1073/pnas.0907434106
|View full text |Cite
|
Sign up to set email alerts
|

Strong-field control and spectroscopy of attosecond electron-hole dynamics in molecules

Abstract: Molecular structures, dynamics and chemical properties are determined by shared electrons in valence shells. We show how one can selectively remove a valence electron from either ⌸ vs. ⌺ or bonding vs. nonbonding orbital by applying an intense infrared laser field to an ensemble of aligned molecules. In molecules, such ionization often induces multielectron dynamics on the attosecond time scale. Ionizing laser field also allows one to record and reconstruct these dynamics with attosecond temporal and subÅngstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(142 citation statements)
references
References 37 publications
2
140
0
Order By: Relevance
“…(28) for NCs {A 1 , A 2 } and NOs {φ 1 , φ 2 }, from which the non-orthogonal orbitals {ψ 1 , ψ 2 } are computed at each time step using Eq. (18). The obtained instantaneous non-orthogonal orbitals, plotted with dashed lines in Fig.…”
Section: B Interpretation Of Ehf Orbitals In Tunneling Ionizationmentioning
confidence: 99%
“…(28) for NCs {A 1 , A 2 } and NOs {φ 1 , φ 2 }, from which the non-orthogonal orbitals {ψ 1 , ψ 2 } are computed at each time step using Eq. (18). The obtained instantaneous non-orthogonal orbitals, plotted with dashed lines in Fig.…”
Section: B Interpretation Of Ehf Orbitals In Tunneling Ionizationmentioning
confidence: 99%
“…[7] for a recent theoretical work on photon emission spectroscopy of hole migration). The alternative techniques of attosecond transient absorption spectroscopy [8] and HHG spectroscopy [9] in their present realizations address the dynamics of outer-valence ionized states. Here we propose a new type of time-resolved attosecond technique, single-photon laser-enabled Auger decay (spLEAD) spectroscopy, that uses a VUV ionizing probe and is particularly suited to characterizing hole migration dynamics in the inner-valence energy region.…”
mentioning
confidence: 99%
“…1 and 4). Based on measurements of ionization by removal of the most weakly bound electron in diatomic and linear triatomic molecules [9][10][11], we expect suppression of ionization in the nodal plane of the LUMO orbital. As is evident from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the case of single-photon ionization, or recombination leading to harmonic emission, it was shown that the measurements reflect the Dyson orbital associated with the ionization [8]. In the case of tunnel ionization of groundstate diatomic molecules, while there is no direct formalism that relates the angle-resolved ionization yields to the molecular orbital structure, the ionization yield as a function of the angle between the laser polarization vector and the molecular axis has been shown to reflect the shape of the orbital from which an electron was removed, i.e., the hole left following ionization [9][10][11][12]. The angle-resolved yields show that ionization is suppressed for cases where the laser polarization lies along the nodal plane of the molecule as a result of destructive interference of the outgoing electron wave [13].…”
Section: Introductionmentioning
confidence: 99%